Penggunaan Rangkaian Media Gambar sebagai Materi Pembelajaran Bahasa Indonesia Bertema Teks Deskripsi di Sekolah Langit Biru Kota Bengkulu untuk Meningkatkan Pembelajaran Bahasa Indonesia - Agustina, Manila; Yuniati, Ira; Suyuthi, Hasmi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of the study is to ascertain the outcomes and challenges encountered by grade 3 pupils at the Langit Biru School in Bengkulu City when composing descriptive prose using a variety of picture media. The descriptive qualitative approach of data analysis is applied. Data gathering methods include documentation, interviews, essay writing skills assessments, and observation. The average score for students' descriptive essay writing abilities, according to the research findings, was 78.8, falling into the good group. The fact that 14 pupils were able to obtain the required KKM score demonstrates this. Students encounter the following challenges: (a) they are still unsure about how to begin writing an essay; (b) they struggle to put relevant words into sentences; and (c) There are still students who cannot read.